Optimalisasi Kemampuan Gerak Dasar Lokomotor dengan Memodifikasi Sarana Pembelajaran PJOK - Karrera Wihda Lupita; Vega Candra Dinata; Zainal Arifin (Syntax Corporation, 2023)
The purpose of this study was to optimize the locomotor basic movement abilities of students in class 4A UPT SDN 144 Gresik for the 2022/2023 Academic Year by modifying the PJOK learning facility. This study used the Classroom Action Research (CAR) method. The data sources in this study were all class 4A students at UPT SDN 144 Gresik for the 2022/2023 academic year. The research subjects were 28 class 4A UPT SDN 144 Gresik students for the 2022/2023 academic year, which were divided into 12 male students and 16 female students. The data collection technique is through tests and measurements of locomotor basic movement abilities based on the Gross Motor Development Test and observation of the process of learning activities. The data analysis technique used in this research is descriptive based on qualitative analysis. The procedure of this research includes planning, acting, observing and reflecting. Based on the results of the research, it was concluded that modifying the learning facilities for Physical Education can optimize the basic locomotor movement abilities of UPT SDN 144 Gresik students in the 2022/2023 Academic Year. From the results of the analysis obtained there was an increase from the initial conditions to cycle I and cycle II, both from increasing locomotor basic movement abilities and the completeness score of learning outcomes. Basic locomotor movement ability in initial conditions (105.61), cycle I (124.86), cycle II (146.25), so that the increase from initial conditions to cycle II was (40.64). The completeness value of learning outcomes in the initial conditions (66.0), cycle I (78.0), cycle II (91.4), so that the increase from the initial conditions to cycle II was (25.4).